A clinical study of pleural effusion and its radiological, biochemical, bacteriological and cytological correlation - N D Khamar; P R Gohil; R N Thacker; U S Gediya (Journal of Integrated Health Sciences)
Introduction: Pleural effusion refers to excessive or abnormal accumulation of fluid in the pleural space. It is a commonly encountered medical problem caused by a variety of underlying pathological conditions. It is important to establish an accurate etiological diagnosis, so that the patient may be treated in the most appropriate and rational manner. Methodology: An observational study was conducted at a tertiary health care center. The pleural effusion was assessed clinically, radiologically, bacteriologically and cytologically. Result: Maximum number of cases of pleural effusion were tuberculous (73%) followed by malignant (12%) and parapneumonic effusion (9%). Pleural fluid cytology for malignant cells was positive in 5 (41.67%) patients out of 12 patients of malignant pleural effusion. Chest pain, breathlessness, cough and fever were common symptoms. Majority of tubercular and malignant effusion had lymphocytes as predominant pleural fluid cells and parapneumonic effusion and empyema had polymorph predominant cells. Conclusion: Tuberculosis is still the most common cause of pleural effusion followed by malignancy. Fluid analysis can give definite clues to the diagnosis. Tuberculosis must be ruled out in all cases of pleural effusion.